Comparative Analysis of Labor Market Dynamics Using Markov Processes : An Application To Informality - Bosch, Mariano (The World Bank, 2007)
This paper discusses a set of statistics for examining and comparing labor market dynamics based on the estimation of continuous time Markov transition processes. It then uses these to establish stylized facts about dynamic patterns of movement using panel data from Argentina, Brazil and Mexico. The estimates suggest broad commonalities among the three countries, and establish numerous common patterns of worker mobility among sectors of work and inactivity. As such, we offer some of the first comparative work on labor dynamics. The paper then particularly focuses on the role of the informal sector, both for its intrinsic interest, and as a case study illustrating the strengths and limits of the tools. The results suggest that a substantial part of the informal sector, particularly the self-employed, corresponds to voluntary entry although informal salaried work may correspond more closely to the standard queuing view, especially for younger workers